Analisis Faktor yang Mempengaruhi Terjadinya Masalah Bendungan ASI pada Ibu Postpartum di Puskesmas Watu Alo - Afrinita, Maria; Suryati, Ns. Yuliana; Jakri, Yohanes; Banul, Maria Sriana (Universitas Malahayati, 2025)
ABSTRACT Breastfeeding is known as one of the most powerful influences on a child's survival, growth and development. Research states that early initiation in the first hour of the first hour can prevent 22% of infant deaths under 1 month of age in developing countries. The achievement of 6 months of exclusive breastfeeding depends on the successful initiation within the first hour. Exclusive breastfeeding during the first 6 months of life, along with complementary foods and continued breastfeeding from 6 months to 2 years, can reduce infant mortality by at least 20%. This study is a quantitative study with a cross sectional design. Data collection was carried out using questionnaires, structured observations that have been tested. The sample in this study is postpartum mothers who experience problems with breast milk dams. The results of the study found that there was a relationship between breastfeeding behavior and the incidence of breast milk dams in postpartum mothers, the results with p-value = 0.016, there was a relationship between breast care and the incidence of breast milk dams with p-value = 0.001 and there was a relationship between breastfeeding motivation and the incidence of breast milk dams. The incidence of breastfeeding dams is related to breastfeeding behavioral factors, the incidence of breastfeeding dams is related to breast care activities during pregnancy, the incidence of breastfeeding dams is related to the motivation of postpartum mothers with the incidence of breastfeeding dams. Keywords: Breast Milk Dam, Determinants of Factors, Postpartum Mother ABSTRAK Pemberian ASI dikenal sebagai salah satu yang memberikan pengaruh paling kuat terhadap kelangsungan hidup anak, pertumbuhan dan perkembangan. Penelitian menyatakan bahwa inisiasi dini dalam 1 jam pertama dalam 1 jam pertama dapat mencegah 22% kematian bayi dibawah umur 1 bulan di negara-negara berkembang. Pencapaian 6 bulan ASI eksklusif bergantung pada keberhasilan inisiasi dalam satu jam pertama. ASI ekskusif selama 6 bulan pertama kehidupan, bersamaan dengan makanan pedamping ASI dan meneruskan ASI dari 6 bulan sampai 2 tahun, dapat mengurangi sedikitnya 20% kematian bayi. Studi ini merupakan studi kuantitatif dengan desain cross sectional. Pengumpulan data dilakukan dengan menggunakan kuesioner, observasi terstruktur yang telah diuji cobakan. Sampel dalam penelitian ini adalah ibu postpartum yang mengalami masalah bendungan ASI. Hasil penelitian didapatkan ada hubungan antara Perilaku menyusui dengan kejadian bendungan ASI pada ibu post partum, hasil dengan pvalue = 0,016, ada hubungan hubungan antara perawatan payudara dengan kejadian bendungan ASI hasil dengan p-value = 0,001 dan ada hubungan motivasi menyusui dengan kejadian bendungan ASI.hasil dengan p-value = 0,02. Kejadian bendungan ASI berhubungan dengan factor perilaku menyusui, Kejadian bendungan ASI berhubungan dengan kegiatan perawatan payudara pada masa kehamilan, Kejadian bendungan ASI berhubungan dengan motivasi ibu post partum dengan kejadian bendungan ASI. Kata Kunci: Bendungan ASI, Determinan Faktor, Ibu Postpartum